Salicylic Acid Versus Glycolic Acid Peel in Active Acne - Aftab, Kanza; Iftikhar, Nadia; Hussain, Majid; Zainab, Zarnab; Mumtaz, Maimoona; Obaid, Shanza (Pakistan Armed Forces Medical Journal, 2022)
Objective: To compare the efficacies of Salicylic acid and Glycolic acid peel in patients with active acne. Study Design: Quasi-experimental study. Setting and Duration of Study: Department of dermatology, Pak Emirates Military Hospital, (PEMH) Rawalpindi Pakistan, Dec 2018 to Jan 2020. Methodology: A total of 300 patients with active acne were included in this study. Patients were randomized into groups by lottery method. Group-A was given 30% Salicylic acid, while Group-B was given 70% Glycolic acid to control active acne. A grading system developed by Hayashi et al, was used to assess the response. A score less than six after 12 weeks was considered a positive response. In addition, the type of treatment and other factors were compared in the patients with and without a positive response after the designated treatment. Results: Out of 300 patients with active acne included in the study, 172 (57.3%) had a positive response, while 128 (42.7%) had not achieved a positive response after the twelve-week treatment. Use of 30% Salicylic acid, lesser duration of acne and more minor age of the patients had a statistically significant relationship with a positive response in the study population (p-value 0.010, 0.005 and 0.001, respectively). Conclusion: A significant number of patients did not respond to standard therapy of acne vulgaris. However, chances of achieving a positive response increase with 30% Salicylic acid instead of 70% Glycolic acid, lesser duration of acnes and young patients have more chances of getting a positive response at the end of the therapy.